Manual Acupuncture or Combination with Vitamin B to Treat Diabetic Peripheral Neuropathy: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Du, Yu zheng; Cao, Can can; Li, Meng dan; Fan, Yi hua; Jia, Peng; Jiang, Hai lun; Li, Yuan (BioMed research international, 2020)
Background and Objective. The efficacy of mecobalamin (vitamin B12) alone in the treatment of diabetic peripheral neuropathy (DPN) is often unsatisfactory, while acupuncture treatment is also controversial. This study compares manual acupuncture to vitamin B in DPN treatment. Methods. Randomized controlled trials on manual acupuncture treatment of DPN were retrieved from the Medline, Web of Science, PubMed, Cochrane Library, EMBASE, CNKI, WanFang, and VIP databases. Extracted research data were summarized in the tables, and methodological assessment was performed using the risk-of-bias assessment tool of Cochrane. Meta-analysis was performed by Revman 5.3, Stata 14.0, and TSA 0.9.5.10 Beta software. Results. A total of 18 randomized clinical trials (RCTs) were recruited: (1) 11 RCTs were acupuncture alone compared with vitamin B; (2) 7 RCTs were acupuncture combined with vitamin B compared with vitamin B, involving 1200 participants. Acupuncture alone improved clinical efficacy (P<0.05) and nerve conduction velocity of the four peripheral nerves: peroneal nerve, tibial nerve, median nerve, and ulnar nerve (P<0.05), but there was no significant difference between the group of acupuncture alone and the group of vitamin B (P=0.36>0.05) in improving median nerve SCV (sensory nerve conduction velocity). Acupuncture combined with vitamin B improved clinical efficacy and nerve conduction velocity of the three peripheral nerves, peroneal nerve, tibial nerve, and median nerve (P<0.05), and decreased the scores of the Toronto clinical scoring system (TCSS) (P<0.05). Conclusion. Acupuncture alone and vitamin B combined with acupuncture are more effective in treating DPN compared to vitamin B. However, more high-quality RCTs on vitamin B combined with acupuncture are required to confirm our results.